2002
DOI: 10.1017/s0025315402005696
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle of Bolinus brandaris and penis and genital duct size variations in a population affected by imposex

Abstract: The reproductive cycle of Bolinus brandaris (Gastropoda: Muricidae) was investigated. Specimens were sampled monthly from a site off Sant Carles de la Ràpita, in the western Mediterranean, between February 1999 and March 2000. A pattern was observed in the reproductive cycle, with two reproductive peaks (April and June–July). The first stages of gametogenesis began in September for males and November for females. Mature males were found from December to April and from June to July. Maximum ripening in fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 9 publications
16
49
0
Order By: Relevance
“…These slight differences in size distribution between collecting sites can be also explained by differences in depth, because for the same species caught in Saint Carles de la Ràpita (Catalan coast), Martín et al (1995) showed that the size distribution was significantly correlated with depth. The present results corroborate Ramón & Amor (2002), who found that both sexes were distributed from 26 mm to 52 mm SLWS. Females were more abundant at lengths between 33 and 40 mm SLWS, but the size structure was similar in both sexes.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These slight differences in size distribution between collecting sites can be also explained by differences in depth, because for the same species caught in Saint Carles de la Ràpita (Catalan coast), Martín et al (1995) showed that the size distribution was significantly correlated with depth. The present results corroborate Ramón & Amor (2002), who found that both sexes were distributed from 26 mm to 52 mm SLWS. Females were more abundant at lengths between 33 and 40 mm SLWS, but the size structure was similar in both sexes.…”
Section: Discussionsupporting
confidence: 93%
“…This observation agrees with those reported for B. brandaris populations collected from Vilanova i la Geltrú and Barcelona (Spain) (Ramón & Amor 2001). In contrast, the same authors (Ramón & Amor 2002), as well as others (Vasconcelos et al 2011), reported that females were more abundant than males in populations of B. brandaris collected off Sant Carles de la Rapità (Tarragona, Spain) and from the Ria Formosa lagoon (Portugal), respectively. Differences in the sex-ratios can be explained by distinct depth distribution between sexes that might affect their availability (Ramón & Amor 2002).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations